Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1093/schbul/sbv076
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Response in Repetitive Transcranial Magnetic Stimulation Trials of Treatment of Auditory Hallucinations in Schizophrenia: A Meta-Analysis

Abstract: Several meta-analyses have assessed the response of patients with schizophrenia with auditory verbal hallucinations (AVH) to treatment with repetitive transcranial magnetic stimulation (rTMS); however, the placebo response has never been explored. Typically observed in a therapeutic trial, the placebo effect may have a major influence on the effectiveness of rTMS. The purpose of this metaanalysis is to evaluate the magnitude of the placebo effect observed in controlled studies of rTMS treatment of AVH, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 44 publications
3
32
2
2
Order By: Relevance
“…9 Moreover, one recently published meta-analysis (21 rTMS studies) showed that the effect size for sham rTMS is 0.29 for the treatment of auditory verbal hallucinations. 56 These high placebo rates question the promising findings from uncontrolled NIBS trials. 40 Second, cognitive measures are highly sensitive to practice effects.…”
Section: Results Of Individual Studies (Outcomes)mentioning
confidence: 99%
“…9 Moreover, one recently published meta-analysis (21 rTMS studies) showed that the effect size for sham rTMS is 0.29 for the treatment of auditory verbal hallucinations. 56 These high placebo rates question the promising findings from uncontrolled NIBS trials. 40 Second, cognitive measures are highly sensitive to practice effects.…”
Section: Results Of Individual Studies (Outcomes)mentioning
confidence: 99%
“…Sixth, as regards the sham condition, as in previous studies [13, 14, 29], we employed the technique of tilting the coil by 90°; in doing so, both the sound and the skin sensation were equivalent to genuine stimulation, but with no effect on the underlying cortex. However, Dollfus et al [30] suggested employing a sham coil, which may be a more reliable method for a placebo procedure. Last, the research group of Bartoli et al [31-34] showed that patients after stroke might be at an increased risk of suffering from depression, insomnia, and suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect multiple factors such as growing public/media attention, more sophisticated technological device set-ups, changes in included patient populations and more realistic sham coils. TMS’s robust placebo responses are not limited to studies of depression and have also been well characterized in other neuropsychiatric fields including schizophrenia 34 , obsessive-compulsive disorder 35 , Parkinson’s disease 36 and chronic pain. 37 Other areas of TMS research such as epilepsy 38 and motor learning 39 have reported more modest placebo responses.…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%